Mechanisms of G2 Arrest in Response to Overexpression of p53 - Taylor, William R. (The American Society for Cell Biology, 1999)
Overexpression of p53 causes G2 arrest, attributable in part to the loss of CDC2 activity. Transcription of cdc2 and cyclin B1, determined using reporter constructs driven by the two promoters, was suppressed in response to the induction of p53. Suppression requires the regions −287 to −123 of the cyclin B1 promoter and −104 to −74 of the cdc2 promoter. p53 did not affect the inhibitory phosphorylations of CDC2 at threonine 14 or tyrosine 15 or the activity of the cyclin-dependent kinase that activates CDC2 by phosphorylating it at threonine 161. Overexpression of p53 may also interfere with the accumulation of CDC2/cyclin B1 in the nucleus, required for cells to enter mitosis. Constitutive expression of cyclin B1, alone or in combination with the constitutively active CDC2 protein T14A Y15F, did not reverse p53-dependent G2 arrest. However, targeting cyclin B1 to the nucleus in cells also expressing CDC2 T14A Y15F did overcome this arrest. It is likely that several distinct pathways contribute to p53-dependent G2 arrest.